Perbedaan Madzhab dalam Menentukan Awal Bulan Hijriah: Studi Krisis atas Pendekatan Hisab dan Rukyah: The Difference in Schools of Thought in Determining the Beginning of the Hijri Month: A Crisis Study on the Approaches of Hisab and Rukyah - Ahmad Muhammad Musta’in Nasoha; Hurin Fikriyyah; Wiwid Farah Dewi; Anisa Fitri Rohimah; Kholifatu Nabila Kurnia Ranadhani (Litera Academica Publishing, 2025)
Abstract The determination of the beginning of the Hijri month occurs in the Islamic world, particularly concerning the use of the methods of hisab (astronomical calculation) and rukyah (direct observation). This difference is not only technical but also rooted in the various Islamic schools of thought (madhabs), which have different approaches to sources of law and epistemology. This study aims to critically examine the differences among the madhabs in determining the beginning of the Hijri month by reviewing the methods of hisab (astronomical calculation) and rukyah (direct observation). The approach used is qualitative with a literature review method on relevant primary and secondary sources. The research findings indicate that the Shafi'i and Hanbali madhabs tend to prioritize rukyah as the main method, while the Hanafi and Maliki madhabs are more flexible in accepting hisab under certain conditions. On the other hand, this difference also has implications for religious decisions in various Muslim countries that have different policies in determining the beginning of the Hijri month. In addition to the fiqh aspect, this study also highlights how the development of astronomical technology plays a role in reconciling these two approaches.As an implication, this research proposes the need for more intensive dialogue and consultation among scholars from different madhabs to find a common ground and solutions that can be accepted by all Muslims. The study also emphasizes the importance of developing a more accurate and integrated Hijri calendar system, utilizing advancements in science and technology. In conclusion, while differences remain, a more inclusive and integrative approach is needed so that Muslims can reach a broader agreement on determining the beginning of the Hijri month without neglecting both the sharia and scientific aspects.